Roles of EP Receptors in the Regulation of Fluid Balance and Blood Pressure - Wang, Lu; Wu, Yiqian; Jia, Zhanjun; Yu, Jing; Huang, Songming (Frontiers in Endocrinology, 2022)
Prostaglandin E2 (PGE2) is an important prostanoid expressing throughout the kidney and vasculature. Despite the diverse effects on fluid metabolism and blood pressure, PGE2 is implicated in sustaining volume and hemodynamics homeostasis. PGE2 works through four distinct EP receptors which are G protein-coupled receptors. To date, pharmacological specific antagonists and agonists of all four subtypes of EP receptors and genetic targeting knockout mice for each subtype have helped in uncoupling the diverse functions of PGE2 and discriminating the respective characteristics of each receptor. In this review, we summarized the functions of individual EP receptor subtypes in the renal and blood vessels and the molecular mechanism of PGE2-induced fluid metabolism and blood pressure homeostasis.